Knowledge and Practice of Nurses towards Oxygen Therapy in the Public Hospitals of Harari Region, Ethiopia - Arif Jamie (Golestan University of Medical Sciences, 2021)
Background: Oxygen therapy refers to the administration of oxygen as a medical intervention. Inadequate oxygen administration may result in serious complications including cardiac arrhythmias, tissue injury and ultimately cerebral damage. The aim of this study was to determine knowledge and practice of nurses on supplemental oxygen therapy in Harari region, Ethiopia. Methods: This cross-sectional descriptive study was performed on all nurses working in three public hospitals in the Harari region, Ethiopia in 2021. A self-administered questionnaire was used to assess nurses' knowledge and practice about oxygen therapy. Demographic information was also collected using the questionnaire. Data were analyzed in SPSS 20 using descriptive statistics. Results: Of 422 participants, 212 (50.2%) were female. The majority of nurses were 20-29 years old (40.5%) and had a Bachelor's degree (69.9%) and 4-6 years of work experience (35.5%). We found that 61.4% and 47.5% of the nurses had good knowledge and practice level about oxygen therapy, respectively. Knowledge about oxygen therapy had no significant association with gender, age, education level, marital status and work experience. Conclusion: Our findings indicate that there is a clear knowledge and practice gap among nurses working in the public hospitals of Harari region, Ethiopia. Therefore, extensive educational and training programs should be offered to nurses to raise their knowledge and practice about oxygen therapy.